IMPLIKASI PEMBATALAN PERDA TERHADAP KETEPATAN PROPORSI TEORI PENEGAKAN HUKUM DALAM SISTEM PERADILAN DI INDONESIA - Fatkhurohman Fatkhurohman (Faculty of Law, Universitas Jenderal Soedirman, 2013)
After the abrogation of a local regulation made by the central government, the local government may make a legal effort called an ‘objection” mechanism. In the on hand, the objection made by the local government shows that a law enforcement may be well made. On the other hand, an unclear concept of law enforcement arises. It is due to the fact that the substance of the 2004 Law no. 4 article 10 on the Justice Power merely regulates 4 (four) matetrs namely: General Justice, Religion Justice, Military Justice and State Administrative Jutsice. Therefore, any dispute on any decision on local regulation abrogration actually is not included in the fourth category in the concerned justice environment. Efforts that may be made is to add authorities to the Supreme Court by arranging justice institution that handle any local regulation dispute, optimizing executive reviews and applying judicial reviews. From streamlining improper theories of the solution on the dispute of Local Regulation abbrogation through the Supreme Court, to find out a way out is a necessity in order to avoid any legal uncertainty. Key words: Local regulation, local regulation abbrogation, objection mechanism